Biomedical Applications of Fluorescent and Magnetic Resonance Imaging Dual‐Modality Probes. (21st November 2018) - Deng, Yun; Xu, Aifei; Yu, Yanhua; Fu, Cheng; Liang, Gaolin
Abstract: Molecular imaging plays a critical role in biomedical research. The combination of different modalities can generate complementary information and provide synergistic advantages over single modality alone. Noninvasive and nonradioactive fluorescent imaging (FI)/magnetic resonance imaging (MRI) dualmodality probes fuse the high sensitivity of FI and the high temporal and spatial resolution and deep‐tissue penetration of MRI, and their increasing applications have been reported in biomedical research and clinical practices, including cell labeling, enzyme activity measurement, tumor diagnosis and therapy, and anatomical localization and real‐time assessment during surgery. Abstract : Attracting light to specific sites : Molecular imaging plays a critical role in biomedical research. Applications of fluorescent imaging/magnetic resonance imaging (FI/MRI) dual‐modality probes in cell labeling, enzyme activity measurements, tumor diagnosis and therapy, and anatomical localization and real‐time assessment during surgery are reviewed.